Comparison of Japan and OECD Countries in Terms of Well-Being Resources - Ince, Fatma (Problemy Ekorozwoju, 2023)
While evaluating the concept of well-being for sustainability, which is defined as the feeling of having the physical and psychological resources necessary for a good life, it is essential to benefit from different perspectives referring to socio-psychological factors or their possible effects as well as financial and economic data. The aim of this study, which deals with the well-being level in terms of sustainability resources, is to evaluate the OECD countries and examine the differences and similarities in Japan, one of the G8 countries. According to the results of the multidimensional scaling analysis conducted for this purpose, Japan is in the same cluster as Luxembourg, which has the highest positive value, while Germany is one of the countries with the highest rate of divergence from other G8 countries in the difference matrix.